Determinants of student performance in the introductory economics course in UP - Gerardo P. Sicat; Kristine Joy S. Briones (University of the Philippines, School of Economics (UPSE), 2009)
Human capital formation in collegiate education can be partly measured by academic performance in a course. This study is based on students enrolled in the introductory course in the University of the Philippines under a single professor for the period 1998 to 2007. Data on the student's performance in the course are linked with a vast amount of collateral information, both collegiate and pre-collegiate, some traced to regional as well as other development factors associated with these backgrounds. Such pre-enrollment data include the student's performance in the UP college admissions test (UPCAT). Student performance is the course is predicted well by the entrance examination scores of the student in the university. Broken down into separate factors, the scores in mathematics, science and reading are highly significant explanatory variables. These factors affirm the importance of factors associated with the student's innate characteristics. In addition, gender does not play a distinctive role in academic performance although females tend to perform better as a group than males. There is a distinguishable difference in the performance of students coming from different course programs. Regional and other economic provincial variables such as mortality and malnourishment rates associated with the student's place of high school origin are a poor predictor of performance. A perceptible increase in performance of student is associated with the improvement of teaching technology that is linked with information technology and the internet.
Keywords: 330; Human capital formation; collegiate education; introductory economics; economic development; college entrance examinations; Humankapital; Studierende; Wirtschaftsstudium; Philippinen